Non-logic devices in logic processes - Ma, Yanjun; Kan, Edwin (Springer, 2017)
This book shows readers how to design semiconductor devices using the most common and lowest cost logic CMOS processes. Readers will benefit from the author's extensive, industrial experience and the practical approach he describes for designing efficiently semiconductor devices that typically have to be implemented using specialized processes that are expensive, time-consuming, and low-yield. The author presents an integrated picture of semiconductor device physics and manufacturing techniques, as well as numerous practical examples of device designs that are tried and true.
Keywords: Metal oxide semiconductors, Complementary.; elektronické knihy; electronic books